Clinical significance of R-TEG in severe burn patients with coagulation dysfunction. Issue 12 (December 2022) - Li, Quan; Zhang, Tiening; Wang, Lingfeng; Li, Fang; Chen, Qiang; Cao, Shengjun; Ba, Te
Abstract: Introduction: The aim of this study was to retrospectively analyze Thrombelastography (TEG) data of severe burn patients to provide a clinical basis for timely diagnosis and treatment of coagulation dysfunction. Methods: The present study comprised burn patients with full thickness TBSA ≥ 60%. The patients included in the study were admitted to the Third Affiliated Hospital of Inner Mongolia Medical University between March 2019 and March 2022 and died within 10 days. Patient demographic and clinical data, including abbreviated burn severity index (ABSI) score, full thickness and overall total surface burn area (TBSA), injury cause, International Society on Thrombosis and Hemostasis (ISTH) score, were retrieved from the electronic medical record system. TEG data (including ACT, K, α, MA and LY30), platelet count (PLT), mean platelet volume (MPV) and platelet distribution width (PDW) data were obtained from the records of included patients for analysis. Results: A total of 9 patients were enrolled. The average burn area was 90.0% TBSA and the full-thickness TBSA was 72.0%. The results showed that α, MA and PLT count values were significantly lower relative to those at obtained throughout admission period (all p < 0.05). PDW and MPV were significantly higher compared with the values at admission (all p < 0.05). ACT time was significantly longer from day 2 after severe burn compared with the ACT time at admission (all p < 0.05). LY30 value from day 3 after severe burn was significantly higher compared with the value at admission ( p < 0.05). One patient was diagnosed with diffuse intravascular coagulation (DIC) on admission, whereas eight patients were diagnosed with DIC on the day of death. Conclusion: Coagulation dysfunction after severe burn is mainly characterized by procoagulant disorders and hyperfibrinolysis, which can be timely detected by TEG. Coagulation after severe burn exhibits a gradual aggravation, and can lead to death of patients.